Frailty Index among Older Adults with Cancer at B.P. Koirala Memorial Cancer Hospital, Chitwan, Nepal - Neupane, Laxmi; Upadhyay, Hari Prasad; Lamichhane, Nirmal (Nepalese Journal of Cancer, 2023)
Introduction: The number of older adults is increasing day by day. This fact implies important health challenges. Frailty level in older adults having cancer is a globally important health issue. The concept of frailty has become gradually more accepted as one of the most important factors particularly in patients with cancer who are receiving treatment. The objective of the study was to find out the frailty index among older adults with cancer admitted for surgery at BPKMCH, Bharatpur, Nepal. Methods: An analytical cross-sectional study was conducted among 111 older adults. Nonprobability purposive sampling technique was used for data collection. Data were collected by face-to-face interview method using Carolina Frailty Index (CFI) developed from a cancer-specific geriatric assessment. Data was entered and analyzed by using SPSS-20, p-value <0.05 was considered as statistically significant. Results: The age of the respondents ranged from 60 to 87 years with mean + SD: 67.46+6.11. Most common site of cancer was gastrointestinal system (47.7%) and the most prevalent co- morbidities in this study were diabetes mellitus (19.8%) and high blood pressure (18.0%). Based on the CFI score, 82.0% were robust, 11.7% were pre-frail and 6.3% were frail. Increasing age (P=0.033) and ethnicity (P=0. 042) were associated with frailty. Conclusion: CFI is a practical way to define oncologic frailty. Though it is only a descriptive study, frailty index revealed by this study would provide valuable baseline information for further researchers.